If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -4(4x + -1) = 94 Reorder the terms: -2 + -4(-1 + 4x) = 94 -2 + (-1 * -4 + 4x * -4) = 94 -2 + (4 + -16x) = 94 Combine like terms: -2 + 4 = 2 2 + -16x = 94 Solving 2 + -16x = 94 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -16x = 94 + -2 Combine like terms: 2 + -2 = 0 0 + -16x = 94 + -2 -16x = 94 + -2 Combine like terms: 94 + -2 = 92 -16x = 92 Divide each side by '-16'. x = -5.75 Simplifying x = -5.75
| -5(7x+7)= | | x^2*5= | | -5n+7n+6-2= | | .13x+.9(x-3)=.01(4x-4) | | -t=9(t+-10) | | 7x-4x-6=-17 | | 0.2n+1.2=2.6 | | x+(-2x+14)=-2 | | 8a-11=-35 | | -[3z-(14z+6)]=6+(10z+7) | | 6(x-1)-9=3x+3(-5+x) | | x-1/2-1=1/3(x-1) | | 111.2x=556 | | 2.85t^2+50t-1000=0 | | 3x+34=154 | | 3.2m-6-3.2m-7= | | y-11=5/7(x-14) | | 5+2x+9=4x-11 | | 17u+4=157 | | 0=Y+2(lnY) | | 14+x+14+x= | | 2x-3y=k | | 16xz+4xy=32 | | -7+x+-7+x= | | 3x(x+26)= | | 8+s=3s | | 19-(2/15) | | (-6+3)+(x-7)= | | 8(3*2-8)+10= | | 4(3y-2)=44 | | .25x-.2(x-1)=5x | | (6x+10)+(6x-1)=180 |